MODERN CHALLENGES TO MILITARY MANAGEMENT. UN SECURITY COUNCIL RESOLUTION 1325 "WOMEN, PEACE AND SECURITY" - Marius-Emanuel CARAGEA (Management & Marketing)
Over time, women, as representatives of the "weaker sex", were marginalized, in the beginning, not being recognized for rights that were considered selfevident for men, and later recognized only to a limited extent or by offering them rights only on half. At the outset of the second half of the 20th century, women’s rights started being acknowledged, gradually, allowing them to be contenders for higher ranking jobs in all aspects of society. The military field followed this trend with somewhat of a delay, it was only at the end of the 20th century that female personnel numbers started growing, with a slow evolution until after the first decade of the 21st century, development driven by “United Nations Security Council Resolution 1325”, adopted in 2000. However, there have been delays in reducing the gender employment gap, seeing how there have been numerous updates regarding the policies on gender equality and discrimination against persons with disabilities, as 13 more resolutions have been issued since the UN resolution of 2000 that complement or influence priorities. This study is based on a comparative analysis regarding the integration of women in military institutions in Romania vs United States of America vs United Kingdom.